The efficacy of serum cell death biomarkers for diagnosing biliary tract cancer - Mitsuru Sugimoto (Nature Portfolio, 2018)
Abstract In this study, we determined the efficacy of the cell death biomarker cytokeratin 18 for diagnosing biliary tract cancer (BTC). We recruited 36 patients with BTC (Malignant group) and 45 patients with benign biliary tract disease (Benign group) for this study. We used M30 and M65 as cell death biomarkers. M30 levels indicate apoptosis, and M65 levels indicate both apoptosis and necrosis. M30 and M65 levels were significantly higher in the Malignant group than in the Benign group (142.4 ± 117.0 vs 48.9 ± 71.2 U/l, P < 0.001; 1513.3 ± 837.4 vs 882.2 ± 831.2 U/l, P = 0.001). The diagnosability of M30 was the highest of the four markers (CEA, CA19-9, M30, M65) (cut-off value: 74.429 U/l, sensitivity: 72.2%, specificity: 77.1%, AUC: 0.771). The sensitivity of M30 (cut-off value: 74.429 U/l) was significantly higher than that of biliary cytology (76% (19/25) vs 12% (3/25), P < 0.001), and the accuracy of M30 was significantly higher than that of biliary cytology (78.3% (36/46) vs 52.2% (24/46), P = 0.015). The sensitivity of M30 (cut-off value: 74.429 U/l) was significantly higher than that of biliary cytology and brush cytology (72.4% (21/29) vs 24.1% (7/29), P < 0.001). In conclusion, cell death biomarkers were increased in patients with BTC, and M30 could efficiently diagnose BTC.